Pendampingan Terintegrasi Legalitas dan Akses Pembiayaan dalam Meningkatkan Kapasitas UMKM Pangan Jamur Kuping Berkelanjutan - Bachtiar Wijaya; Diana Dwi Kusumasari; Titisari Ambarwati; Sudarmiatin Sudarmiatin; Ruly Wiliandri (Faedah: Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
This community service activity aims to increase the business capacity of the wood ear mushroom food MSME through integrated mentoring on business legality and access to financing. The subject of the activity was the Brother Farm MSME in Kediri Regency, which initially ran its business informally without adequate legality and had limited access to formal financing. The method used was a participatory approach with activity stages including: initial observation and problem identification, mentoring in creating a Business Identification Number (NIB), mentoring in understanding halal certification, mentoring in processing Fresh Food of Plant Origin (PSAT) permits, and education on access to financing through the People's Business Credit (KUR) scheme. Data collection techniques were carried out through observation, interviews and documentation, while data analysis used a qualitative descriptive approach by comparing conditions before and after mentoring. The results of the activity showed that the MSME successfully obtained business legality in the form of a Business Identification Number and Fresh Food of Plant Origin permits and experienced an increase in understanding regarding halal product guarantees and access to formal financing. This integrated mentoring had a positive impact on increasing consumer confidence, expanding market opportunities, and business readiness in accessing capital. Thus, this activity is able to encourage business transformation towards a more formal, structured and sustainable condition (SDG 8 and SDG 12) thereby contributing to increasing the competitiveness of food MSMEs.